2020
DOI: 10.1088/1742-6596/1624/3/032050
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Impacts of the COVID-19 Pandemic on China’s Container Ports Based on AIS Big Data

Abstract: To quantitatively analyse the impacts of the COVID-19 pandemic on China’s container ports, the berthing ships are mainly investigated by the big data of Automatic Identification System (AIS). First, the methods of AIS data acquisition, cleaning and statistical analysis are introduced. Then the sample ports of Shanghai, Ningbo-Zhoushan and Tianjin are selected, and the monthly ratios of key indicators such as the number of berthing ships and berthing time are calculated by AIS analysis system. Finally, the nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The results prove that the losses of global maritime trade were 7.0% to 9.6% during the first eight months of 2020, and ports with specific supply chains (e.g., oil and vehicle manufacturing) experienced larger losses in the context of the epidemic. Taking Shanghai port, Ningbo-Zhoushan port, and Tianjin port as examples, Zhu et al (2020) compare the number of arriving ships and the berth time of ships of container vessels between 2019 and 2020. Numerical results suggest that the COVID-19 pandemic significantly reduces the average berth time of ships, while the number of ships arriving at China’s ports is not affected.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results prove that the losses of global maritime trade were 7.0% to 9.6% during the first eight months of 2020, and ports with specific supply chains (e.g., oil and vehicle manufacturing) experienced larger losses in the context of the epidemic. Taking Shanghai port, Ningbo-Zhoushan port, and Tianjin port as examples, Zhu et al (2020) compare the number of arriving ships and the berth time of ships of container vessels between 2019 and 2020. Numerical results suggest that the COVID-19 pandemic significantly reduces the average berth time of ships, while the number of ships arriving at China’s ports is not affected.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results showed that vessel activity decreased by 69 % during the lockdown. Zhu et al (2020) used monthly container port calls and berthing time data derived from the AIS from January to April 2020, and selected Shanghai, Ningbo-Zhoushan and Tianjin as sample ports. When they compared the data from 2020 with that from the previous year, they found that the number of ships arriving at Chinese ports was not significantly affected; but, the average berthing time of ships at port decreased significantly from January to April 2020.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the spread of the COVID-19 pandemic, the volume of maritime cargo transportation has shrunk significantly [4][5][6] in order to effectively prevent the spread of the pandemic at sea. However, affected by the internal demand of economic recovery in various countries, sea freight volume has steadily increased in the second half of 2020.…”
Section: Introductionmentioning
confidence: 99%